(untitled) (Voice: A Biannual & Bilingual Journal, 2025)
This study explores the impact of leadership styles on the job satisfaction of bank employees in Nepal, using quantitative data collected up to December 2024. Leadership styles, including transformational, transactional, and laissez-faire, were analyzed for their effects on employee satisfaction across commercial banks. A structured questionnaire was distributed among 300 employees from 15 different banks. Using statistical tools such as SPSS, correlation and regression analyses were performed. The findings show that transformational leadership has a significant positive effect on job satisfaction, while laissez-faire leadership negatively impacts it. This study provides practical implications for leadership development in Nepalese banks.